PELE: the Planetary Analogs & Exobiology Lava Tube Expedition - Kopacz, Nina; Baque, Mickael; Csuka, Joleen; Vilhelmsson, Oddur; Neubeck, Anna; Singh, Abhijeet; Iakubivskyi, Iaroslav; Callac, Nolwenn; Dapkevicius, Maria; Geppert, Wolf (2018)
Lava tubes on Earth represent some of the most enticing Martian analog environments when investigating the possibility of past or present life on Mars. Lava tubes provide stable, sheltered environments which are isolated and protected from the radiation on the surface. The microbial mats in these caves further regulate the environment for life, allowing various microbial communities with different metabolisms to coexist. This adaptation is so successful, one could imagine it might occur on other planets, with other biologies, and perhaps with other fundamental chemistries [1]. The PELE team has investigated lava caves on Terceira Island, the Azores, and in Iceland. The project aims to correlate biological and mineralogical data to describe the interactions between the microbes and their geological substrates, to identify microbe-specific speleothems as biosignatures (Figure 1), to map the gradients of light, nutrients, and biodiversity, and to develop a sampling technique in these fragile environments. This is achieved with a combination of DNA sequencing, mass spectrometry, and XRF, XRD, and Raman spectroscopy. The work will serve as an indication of what kind of life, or remnants of life, we might expect to find in lave tubes on Mars.